2017
DOI: 10.1093/pubmed/fdx005
|View full text |Cite
|
Sign up to set email alerts
|

Exploring suicidal behaviours by probation clients—a qualitative near-lethal study

Abstract: Suicide prevention strategies must be tailored to the needs of probation clients across the UK. Mandatory training for probation staff is recommended to help reduce suicides, and support from external agencies should be sought where possible.

Help me understand this report

Search citation statements

Order By: Relevance

Paper Sections

Select...
2
1
1

Citation Types

2
21
0

Year Published

2018
2018
2023
2023

Publication Types

Select...
4

Relationship

0
4

Authors

Journals

citations
Cited by 4 publications
(23 citation statements)
references
References 26 publications
2
21
0
Order By: Relevance
“…They highlight the need for further awareness-raising amongst frontline probation staff of sharing crucial information; something that would be missed with high-level analysis of Delius records. An alternative would be to conduct interviews with people who have attempted suicide whilst on probation supervision, as per Mackenzie et al ( 2018 ), or to speak with family members who have had a relative die whilst under supervision in the community. This would reflect the methodology adopted by the PPO following a death in custody or the EHRC when conducting their inquiry into the deaths of adults with mental ill health in custodial settings (EHRC, 2015 ).…”
Section: Discussionmentioning
confidence: 99%
See 1 more Smart Citation
“…They highlight the need for further awareness-raising amongst frontline probation staff of sharing crucial information; something that would be missed with high-level analysis of Delius records. An alternative would be to conduct interviews with people who have attempted suicide whilst on probation supervision, as per Mackenzie et al ( 2018 ), or to speak with family members who have had a relative die whilst under supervision in the community. This would reflect the methodology adopted by the PPO following a death in custody or the EHRC when conducting their inquiry into the deaths of adults with mental ill health in custodial settings (EHRC, 2015 ).…”
Section: Discussionmentioning
confidence: 99%
“…More recently still, Mackenzie, Cartwright and Borrill ( 2018 ) conducted research with seven probation clients who had attempted suicide. Their participants suggested that bereavement, loss of control over their mental state or situation, difficulties relating to their probation sentence, issues around trusting authorities, and an inability to disclose suicidal feelings were linked to their suicidal feelings and behaviours.…”
Section: What Do We Already Know About Suicide In Community Justice Smentioning
confidence: 99%
“…This is not surprising given the difficulty to reach this "group" of people and the sensitivity that is required to carry out this type of research. An exception is an interview study with seven people who made a "near-lethal suicide attempt" whilst on probation (Mackenzie et al 2018). These interviews suggest there is a relationship between suicidal feelings and experiences of loss, including bereavement.…”
Section: Deaths Following Releasementioning
confidence: 99%
“…These interviews suggest there is a relationship between suicidal feelings and experiences of loss, including bereavement. Furthermore, participants found it difficult to disclose these types of feelings due to trust issues and cynicism concerning the Criminal Justice System (Mackenzie et al 2018). Participants also emphasised that having a purpose in life including feeling valued by family or friends or having a job decreased suicidal thoughts (Mackenzie et al 2018).…”
Section: Deaths Following Releasementioning
confidence: 99%
“…Rather, investigations should be about seeking to identify systemic problems which might be hindering practitioners' ability to prevent suicide: this might be inadequacies in training, risk assessment procedures or issues around data collection. There is a small body of knowledge about who is most likely to die whilst under probation supervision (Borrill et al, 2017;Cook and Borrill, 2015;Mackenzie et al, 2018) but more needs to be done and doing more reviews and investigations will augment our understanding in this area. The range and number of investigations into prison deaths means we have a good understanding of why people die in prison.…”
mentioning
confidence: 99%